In vitro antioxidant and in vivo hypoglycemic activity of biophenols and polyunsaturated fatty acids from Vitis vinifera L. muscat and quebranta seeds from the Valley of Ica-Peru - Angel T. Alvarado; Ana María Muñoz; Nesquen Tasayco-Yataco; Fabricio Gamarra-Castillo; Roberto O. Ybañez-Julca; María R. Bendezú; Haydee Chávez; Jorge A. García; Felipe Surco-Laos; Elizabeth J. Melgar-Merino; Pompeyo A. Cuba-Garcia; Patricia Castillo-Romero; et al. (Pensoft Publishers, 2023)
Currently, there is a greater interest in using natural products in various chronic diseases such as type 2 diabetes. However, these investigations have not considered the components of grape seeds. In this context, the current study explored the in vitro antioxidant and in vivo hypoglycemic activity of biophenols and total polyunsaturated fatty acids (PUFA) from Vitis vinifera L. muscat and quebranta seeds from the Ica Valley, Peru. The total polyphenol content (TPC) of muscat (1.57±0.015 mg GAE/g) and quebranta (1.43±0.015 mg GAE/g) seeds was estimated by the Folin-Ciocalteu method. In vitro antioxidant activity was determined by DPPH• free radical assay for muscat and quebranta (IC50: 38.60±0.624 µg/mL and 42.83±0.306 µg/mL, respectively) and by FRAP 0.79±0.030 μg TEAC/g for muscat and 0.61±0.038 μg TEAC/g for quebranta. After inducing experimental hyperglycemia with alloxane in Rattus norvegicus strain Holtzman, treatment was carried out for 7 days and glucose levels were measured at 1, 2 and 4 hours. At a dose of 500 mg/kg, orally, of biophenols/PUFA from muscat and quebranta seeds, a hypoglycemic effect was observed; whose results were verified with the Shapiro-Wilk test (p-value > α = 0.05), Tukey's multiple comparisons test (p-value 0.0001 < α = 0.05), Student's T with p-value < α = 0.05 at 1 hour for days 1 to 6, and p-value 0.999 > α = 0.05 for 2 and 4 hours on day 7, indicates a small probability of difference; in ANOVA results the mean difference is significant (p-value 0.0001 < α 0.05). The Pearson analysis found a strong correlation [0.50 ≤ (0.9530-0.9827) < 1.0] between glibenclamide/biophenols-PUFA glucose levels. Current data show an in vitro antioxidant effect and hypoglycemic activity of the seeds of grapes of the muscat and quebranta varieties. Graphical abstract